An Assessment of Endoscopic and Concomitant Management of Acute Variceal Bleeding at a Tertiary Care Centre. (2007) - Singh, H; Targownik, LE; Ward, G; Minuk, GY; Bernstein, CN
Abstract : BACKGROUND: Several therapies have been demonstrated to be beneficial in the management of acute variceal bleeding (AVB). The aim of the present study was to characterize the use of these therapies at a Canadian tertiary care centre. PATIENTS AND METHODS: A comprehensive chart review was performed to assess the management of all adult cirrhotic patients with AVB who were admitted to a university-affiliated, tertiary care centre between April 2001 and March 2004. RESULTS: A total of 81 AVB patients were identified with a mean age of 53.7±13.2 years and a median model for end-stage liver disease score of 14. Endoscopy was performed within 8.2±7.6 h of admission. Variceal banding was performed for 87% of patients with esophageal varices, which were the most common source of bleeding (80%). Octreotide was used in 82% of patients for a mean duration of 74.3±35.4 h; prophylactic antibiotics were used in 25% of patients and beta-blockers were used in 24% of patients without any contraindications. Follow-up endoscopy was arranged for 46 of 71 (65%) survivors. Prophylactic antibiotic use was associated with the presence of ascites, while beta-blockers were used more often in the last year of the study. CONCLUSIONS: There is a disconnection between the use of evidence-based recommendations and routine clinical practices in the management of AVB. Deficiencies identified include the lack of use of prophylactic antibiotics and beta-blockers, variable use of octreotide and inadequate follow-up recommendations. There is a need to identify measures to improve the process of care for patients with AVB which would ensure optimal management of these patients.